Empowering Women in Ketapang Village: The Role of Students as Agent of Change - Kirana, Chandra; Yusuf, Amin (Universitas Pahlawan Tuanku Tambusai, 2025)
Ketapang Village faces issues of gender inequality, such as women’s low income, limited understanding of women’s roles, and lack of awarness about education and mental health. This research used a descriptive qualitative approach involving students, village government, women’s empowerment participants, and community leaders. The study found that students play a key role as agents of change, social control, iron stock, and moral force in implementing women’s empowerment throught strategies such as dismantling role myths, skills training, and providing educational opportunities. Supporting factors include community and government support, relationship between students and participants, and external cooperation while inhibiting factors include time and locations constraints. This research offers knowledge on how to improve gender equality through women’s empowerment.